Age-dependent change in attention paid to vocal exchange rules in Japanese macaques. (July 2017) - Bouchet, Hélène; Koda, Hiroki; Lemasson, Alban
Abstract : The mechanisms underlying vocal development in nonhuman primates, so-called 'nonlearners', are of special interest because they give an insight in how social factors can shape the expression of an already genetically determined vocal repertoire. Interestingly, recent studies suggest that the acquisition of the complex rules governing vocal exchanges (i.e. context-specific temporal and structural acoustic adjustments) may result from a socially guided development process, with social experience and parental selective feedback playing a key role. Among those conversational rules, call matching is a particularly remarkable phenomenon in Japanese macaques, Macaca fuscata, with interacting adult females matching the frequency range pattern of their own call with another female's preceding call. Here, we investigated whether fine-tuned acoustic adjustments during vocal exchanges in Japanese macaques are subject to developmental processes, specifically testing for the ability of individuals of different age classes to discriminate between vocal exchanges respecting, or not, the matching rule. We performed playback experiments in 10 adult and 10 1-year-old captive Japanese macaque females. Each subject was successively exposed to two stimuli: a pair of calls respecting call matching (i.e. two calls from two individuals with matched frequency ranges) and another pair of calls that did not. Adults discriminated better than juveniles whether stimuli respected the call-matching rule or not, and displayed significantly different levels of interest towards each stimulus type. The latency to look towards the loudspeaker was shorter, and the duration of the directed gaze was longer, after the playback that violated the matching expectation in every adult, but not in juveniles which seemingly displayed a random gaze response. Our findings support the conclusion that the matching rule is relevant for adults, but not for socially inexperienced young monkeys which may not have had enough experience of the conversational rules governing vocal exchanges. Highlights: Japanese macaques perform call matching during vocal exchanges. Playback experiments were conducted in 10 adult and 10 1-year old females. Only adults discriminated whether stimuli respected the call-matching rule or not. Adults reacted faster and stronger after a violation of the matching expectation. The matching rule seems relevant for adults but not for inexperienced juveniles.